2013
DOI: 10.1093/cercor/bht331
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adaptation of Descending Motor Tracts in Musicians

Abstract: Between-group comparisons of musicians and nonmusicians have revealed structural brain differences and also functional differences in motor performance. In this study, we aimed to examine the relation between white matter microstructure and high-level motor skills by contrasting 2 groups of musicians with different instrumentspecific motor requirements. We used diffusion tensor imaging to compare diffusivity measures of different corticospinal motor tracts of 10 keyboard players, 10 string players, and 10 nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 63 publications
4
59
0
Order By: Relevance
“…Human studies show that the structure of specific white matter tracts are associated with functional recovery after stroke, and can respond to behavioral activity 35, 36. The relationship of white matter tract structure and axonal sprouting has not been determined.…”
Section: Behavioral Activity Shapes Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies show that the structure of specific white matter tracts are associated with functional recovery after stroke, and can respond to behavioral activity 35, 36. The relationship of white matter tract structure and axonal sprouting has not been determined.…”
Section: Behavioral Activity Shapes Tissue Regenerationmentioning
confidence: 99%
“…It is quite possible that a rehabilitation therapy may affect white matter structure and myelination, and not affect axonal terminal fields; or that axonal terminal fields may be affected and not gross structure of the myelin tract; or that both are affected by the same behavioral therapy after stroke. Because both myelinated fiber tracts and axonal terminal fields are sensitive to behavioral modulation,29, 36, 38 both are likely altered to some degree after stroke and through neurorehabilitative therapies. But at present, the role of behavioral activity in modulating white matter structure after stroke has not been determined in animal models and only larger white matter tracts can be studied in humans 39…”
Section: Behavioral Activity Shapes Tissue Regenerationmentioning
confidence: 99%
“…These are most striking in the posterior limb of the internal capsule. They have also identified differences between musician groups, with a difference seen between keyboard players and string instrumentalists [34]. Between-group…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 98%
“…Bengtsson et al [33] and Rueber et al [34] have found structural differences in the corticospinal tract between musicians and nonmusicians. These are most striking in the posterior limb of the internal capsule.…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 99%
See 1 more Smart Citation